Education for Real-World Data Science Roles (Part 2): A Translational Approach to Curriculum Development - Liz Lyon; Eleanor Mattern (International Journal of Digital Curation, 2017)
This study reports on the findings from Part 2 of a small-scale analysis of requirements for real-world data science positions and examines three further data science roles: data analyst, data engineer and data journalist. The study examines recent job descriptions and maps their requirements to the current curriculum within the graduate MLIS and Information Science and Technology Masters Programs in the School of Information Sciences (iSchool) at the University of Pittsburgh. From this mapping exercise, model ‘course pathways’ and module ‘stepping stones’ have been identified, as well as course topic gaps and opportunities for collaboration with other Schools. Competency in four specific tools or technologies was required by all three roles (Microsoft Excel, R, Python and SQL), as well as collaborative skills (with both teams of colleagues and with clients). The ability to connect the educational curriculum with real-world positions is viewed as further validation of the translational approach being developed as a foundational principle of the current MLIS curriculum review process